TECHNICAL ANALYSIS AS THE BASIS FOR DECISION MAKING IN STOCK INVESTMENT IN PT. BANK MESTIKA DHARMA.TBK IN THE INDONESIAN CAPITAL MARKET (DURING THE COVID PANDEMIC JANUARY 2020 - JUNE 2021) - Tika Denisa Simanjuntak; Isfenti Sadalia; Nisrul Irawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study uses a quantitative approach to making stock investment decisions using the Moving Average Convergence Divergence indicator and the Stochastic Oscillator indicator by recording sell signals and buy signals and then testing the effectiveness of buy signals and sell signals from the two indicators. This research will be analyzed using the investing.com chart analysis platform. Based on research that has been conducted by researchers, it can be concluded that: 1. From graphic analysis at PT Bank Mestika Dharma Tbk, the Stochastic Oscillator indicator provides a total of 65 signals consisting of 35 buy signals and 30 sell signals while the MACD indicator provides 19 signals consisting of 10 bell signals and 9 sell signals from. 2. The Stochastic Oscillator indicator provides a better level of accuracy with an accuracy rate of 68%, while the MACD indicator has an accuracy rate of 58%. 3. The Stochastic Oscillator indicator has proven to be superior for analyzing stocks with a sideways trend, as experienced by PT Bank Mestika Dharma Tbk during the current economic crisis.